Penggunaan Metode Drill Dalam Pembelajaran Balāgatul Qur'ān Di Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Muhammadiyah Surakarta Tahun Akademik 2015/2016 - Husnul Khatimah, Hasna; , Drs. Najmuddin Zuhdi, M.Ag (2016)
Al-Qur'an is the most supreme miracle of Rasulullah saw. The miracle of al-Qur'an can be seen from its language. The language contains a very beautiful literary value. When al-Qur'an was descended, there were many meanings that could not be understood directly by people, therefore, knowledge which can convey clearly the implied meanings in al-Qur'an is badly needed. One of knowledges is Balāgatul Qur'ān knowledge. University Muhammadiyah of Surakarta is an Islam based college that has study program of Islamic Religion Education (PAI). One aim is to produce competent graduates as teachers of Islamic Religion Education (PAI) in junior and senior high school. As a prospective PAI competent educator, study program of PAI equipping students with the knowledge of Balāgatul Qur'ān. One of the methods used in the learning of Balāgatul Qur'ān is a method of drill. This method is used as a reinforcement of a lecture. As for the intended use of the drill method is to make students more proficient in identifying the verses of al-Qur'ān containing bayān, ma'ānī, and badī', thus facilitate the achievement of learning objectives. The purpose of this research is to describe the implementation of the method of drill in the learning of Balāgatul Qur'ān in the study program of PAI FAI UMS in the academic year 2015/2016, and its strenghts and weaknesses. This research is a field research using a qualitative approach. The data collection have used the methods of interview, observation, and documentation. Meanwhile, the method of data analysis have used descriptive qualitative analysis thorugh three stages: data reduction, data display, and conclusion. The conclusion drawing used the deductive-inductive method. Based on the data from the results of the research, it can be concluded that the implementations of the method of drill in the learning of Balāgatul Qur'ān in the study program of PAI FAI UMS in the academic year 2015/2016 are as follow: first, the lecturer explains the learning material; second, the lecturer gives examples related to the learning materials; third, the lecturer gives opportunity to ask questions related to the materials which have not been understood, the lecturer gives exercise to the students; fifth, the lecturer corrects and clarifies the answer from every student. Then, the strengths of the method of drill are: easing in understanding the materials which are explained, reinforcing the memorizing power on the given materials, sharpening the skill in writing sentences containing balāgah, able to know directly examples from al-Qur'an, understanding more the meanings of al-Qur'an verses, increasing the students' understanding on the given material, training the students to learn autonomously, therefore the lecturer can know whether the learning is successful or not. Meanwhile, the weaknesses are: the exercises which are often given can cause boredom on the students, reducing the students' initiative.